Highly efficient and thermally stable red emitting CaGdMgNbO6:Mn4+ double perovskites for indoor plant growth LEDs. (June 2022) - Han, Bingjie; Yang, Xinghua; Jiang, Yuhan; Li, Zhiang; Shen, Yu; Chang, Xinyu; Ren, Jing; Gao, Shuai
Abstract: Nowadays, more and more attention has been paid to artificial lighting sources for plant growth. In this paper, transition metal Mn 4+ activated CaGdMgNbO6 (CGMNO:Mn 4+ ) red phosphor was prepared high temperature solid state method. The crystal structure and cell parameters of novel CGMNO host were analyzed. The experimental results indicated that CGMNO:Mn 4+ phosphor exhibit an emission band (701 nm), which belongs to the 2 Eg → 4 A2g transition of Mn 4+ . The concentration quenching occurs when Mn 4+ doping concentration is greater than 0.5 mol%. The variable temperature emission spectra proved that the emission intensity of CGMNO:0.005Mn 4+ at 423 K maintained 75.2 % of that at 298 K. The CIE color coordinates and IQE of CGMNO:0.005Mn 4+ are (0.7136, 0.2863) and 49.45 %, respectively. Finally, a LED device was packaged with CGMNO:0.005Mn 4+ phosphor and a high-power chip (440 nm), the LED device shows stable electroluminescence intensity under different currents driving. All the results indicate that phosphors are suitable for lighting contemporary plant growth. Graphical Abstract: ga1